Are CEO and CFO share purchases equally informative in a post-MAR framework? : CASE: Helsinki Stock Exchange - Kilpinen, Aapo (My University, 2021)
Significant positive abnormal returns have been found to follow insider purchases in the stock market. In addition, it has been found that so called “core-insiders” engage in purchases following higher abnormal returns than “non-core insiders”. When further dissecting the “core-insider” group, the CFO in particular has been found to outperform the CEO. Long-term abnormal returns following the insider purchases are thought to be the consequence of insider purchases containing information about the company’s future performance. In July 2016, the Market Abuse Regulation set by European Union in 2014 (EU, N:o 596/2014), came into effect. After the regulation was implemented, the issuer of a stock is obliged to report the trades conducted by its insiders. This leads to a public access to insider trading information. If insider purchases are informative & carry a positive signal and this information is now public, one should be able to generate positive abnormal returns by mimicking these purchases. However, no extensive research has been conducted in the Helsinki Stock Exchange on the subject and no research at all has been conducted post-MAR. Thus, to confirm the informativeness of the insiders’ purchases in a post-MAR period, this study is conducted. The research adopts an event study method combined with a regression analysis to explain the event study’s results. In addition, a CEO of a company listed in the Helsinki Stock Exchange is interviewed to get further insight on the subject. The results reveal that the interpretation of an insider purchase is not straightforward regarding the stock’s performance. Contrary to previous studies, only the CEOs appear to generate statistically significant positive abnormal returns while the CFOs abnormal returns are not statistically different from zero. In addition, the regression analysis revealed that purchases in Small-Cap companies by the CEO generated very high positive 12-month abnormal returns as did CEO purchases in Mid-Cap companies, however milder than the Small-Cap purchases. Large-Cap purchases appeared uninformative, as did all CFO purchases. Interestingly, the market appeared to treat all insider purchases as informative reflected by the short-term abnormal returns concentrated on the announcement date of the purchases. Based on the 12-month abnormal returns, this approach appears to be unfounded.

Merkittävien positiivisten epänormaalien tuottojen on havaittu seuraavan sisäpiirin ostoja osakemarkkinoilla. Niin kutsuttujen ”ydinsisäpiiriläisten” ostojen on lisäksi havaittu tuottavan muita sisäpiiriläisiä suurempia epänormaaleja tuottoja. Tarkentamalla analyysiä ydinsisäpiiriin, on havaittu, että talousjohtaja tekee suurempia epänormaaleja tuottoja toimitusjohtajaan verrattuna. Pitkän aikavälin epänormaalien tuottojen oletetaan johtuvan sisäpiiritiedosta, mikä merkitsee sisäpiirin ostojen sisältävän informaatiota yhtiön tulevaisuuden suorituskyvystä. Euroopan Unionin säätämä Markkinoiden väärinkäyttöasetus MAR (EU, N:o 596/2014) tuli voimaan Suomessa pääsääntöisesti 3.7.2016. Asetuksen johdosta osakkeen liikkeellelaskija on velvoitettu ilmoittamaan sen sisäpiiriläisten suorittamat kaupat, minkä johdosta sisäpiirin kaupat ovat julkista tietoa. Mikäli sisäpiirin kaupat ovat julkista tietoa ja sisäpiirin ostot ovat informatiivisia sekä kätkevät positiivisen signaalin yhtiöstä, sijoittajan pitäisi pystyä ansaitsemaan positiivisia epänormaaleja tuottoja seuraamalla sisäpiirin ostoja. Sisäpiirin kaupankäyntiin liittyvä tutkimus nimenomaan Helsingin pörssissä on kuitenkin hyvin rajattua, eikä yhtään tutkimusta ole toteutettu MAR:n voimaantulon jälkeen. Tämän tutkimuksen tarkoitus on vahvistaa sisäpiirin ostojen informatiivisuus myös Helsingin pörssissä. Tutkimusmetodeina ovat tapahtumatutkimus epänormaalien tuottojen laskemiseen ja regressioanalyysi tapahtumatutkimuksen tuloksien selittämiseksi. Lisäksi, tutkimuksessa haastateltiin Helsingin pörssin listayhtiön toimitusjohtajaa sisäpiirinäkökulman saamiseksi. Tutkimustulokset osoittavat, ettei sisäpiirin ostojen tulkitseminen ole täysin yksioikoista. Vastoin aiempia tutkimuksia, vain toimitusjohtaja tekee tilastollisesti merkittäviä positiivisia epänormaaleja tuottoja. Talousjohtajan tekemät epänormaalit tuotot eivät poikkea tilastollisesti merkittävästi nollasta. Syventämällä analyysiä huomataan, että erityisesti toimitusjohtajan tekemät ostot pienyhtiöissä tekevät erittäin suuria 12kk epänormaaleja tuottoja kuten myös toimitusjohtajien ostot keskisuurissa yhtiöissä, kuitenkin pienemmällä informaatioarvolla kuin pienyhtiöissä. Suurissa yhtiöissä sekä toimitus- että talousjohtajan ostot vaikuttivat epäinformatiivisilta. Markkina kuitenkin kohtelee kaikkia sisäpiirin ostoja yhtä informatiivisena, mikä näkyy lyhyen aikavälin epänormaalien tuottojen kautta. Perustuen tutkimuksessa havaittuihin 12kk epänormaaleihin tuottoihin, markkinoiden lähestymistapa vaikuttaa virheelliseltä.
Keywords: Insider trading, Market Abuse Regulation